Comparison of sexual development with sociodemographic and hematological parameters in multi-transfused Patients of β-thalassemia Major - Muneer, Rida; Ghazanfar, Saqlain; Faisal, Muhammad; Shahid, Zia; Hassan, Sarmad; Kiany, Javeria Arshad; Sheharyar Khan, Muhammad; Shuaib, Atifa (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Background: β-thalassemia major encompasses a wide range of hematological and endocrinological complications. High levels of serum ferritin in individuals with β-thalassemia indicate transfusion-related complications including significant iron overload, which can contribute to endocrine disorders such as hypogonadism and subsequent sexual underdevelopment. Therefore, the aim of our study is to investigate the association of sexual development with sociodemographic and hematological parameters in multi-transfused Patients of β-thalassemia Major. Materials and Methods: This multicentric cross-sectional study consisted of 147 β-thalassemia patients who got enrolled. The sexual development of the participants was evaluated utilizing the Patterson staging system. Data regarding hematological and other demographic variables were collected. Statistical analyses was done using SPSS version 26. Data analysis was done using independent-samples t-test, chi-square test was used for the analysis of collected data. Results: Among the total of 147 patients, 79(53.74%) were males and 68(46.26%) were females. Based on the Patterson staging system, 63(42.85%) of the patients were in the pre-pubertal, early pubertal and mid pubertal/sexually under-developed stage, while 84 (57.15%) of the patients were in the pubescent and post-pubescent/sexually developed stage. Based upon serum ferritin level stratification there was a significant different in sexually developed and underdeveloped patients. Conclusion: Increased serum ferritin levels resulting from transfusion in β-thalassemia is significantly associated with hypogonadism in these patients.